2015
DOI: 10.5089/9781513586205.001
|View full text |Cite
|
Sign up to set email alerts
|

Housing Price and Household Debt Interactions in Sweden

Abstract: Sweden is experiencing double-digit housing price gains alongside rising household debt. A common interpretation is that mortgage lending boosted by expansionary monetary policy is driving up house prices. But theory suggests the value of housing collateral is also important for household's capacity to borrow. This paper examines the interactions between housing prices and household debt using a three-equation model, finding that household borrowing impacts housing prices in the short-run, but the price of hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 33 publications
1
29
1
Order By: Relevance
“…In contrast, other empirical studies have found evidence of bubbles, e.g. Turk (2015), the European Commission Report (2016), the IMF (2016) and UBS (2016) for Sweden; Case and Shiller (2003), Wheaton and Nechayev (2008), Bourassa et al (2016) and Nneji et al (2013) for the USA; Oikarinen (2009) for Helsinki, Black et al (2006) for the UK; and Ambrose et al (2013) for Amsterdam.…”
Section: Introductionmentioning
confidence: 89%
“…In contrast, other empirical studies have found evidence of bubbles, e.g. Turk (2015), the European Commission Report (2016), the IMF (2016) and UBS (2016) for Sweden; Case and Shiller (2003), Wheaton and Nechayev (2008), Bourassa et al (2016) and Nneji et al (2013) for the USA; Oikarinen (2009) for Helsinki, Black et al (2006) for the UK; and Ambrose et al (2013) for Amsterdam.…”
Section: Introductionmentioning
confidence: 89%
“…This is in line with Nizar's (2015) findings that housing prices are significant, thus the increase in housing prices will further increase debt. Another study done by Turk (2015) found that growth in housing prices will moderate to be broadly in line with household debt growth. This result is supported by Jacobsen & Naug (2004) who found that household debt may increase further because higher house prices may result in higher final wealth and better borrowing conditions.…”
Section: Concept Of House Price Index With Household Debtmentioning
confidence: 94%
“…The result showed that developments in the short run are influenced by changes in long term interest rates, and declines in interest rates explain the expansion of households' borrowed funds. Turk (2015) stated that declining interest rates also explain the rise of household debt in Sweden. This result is supported by Mutezo (2015) who revealed evidence of the existence of a long run relationship between household debt and interest rates.…”
Section: Concept Of Household Debtmentioning
confidence: 99%
“…Some studies Þ nd a cointegrating relationship between real house prices and their fundamentals (e.g. Gerlach and Peng, 2005;Gimeno and Martínez-Carrascal, 2006;Égert and Mihaljek, 2007;Oikarinen, 2009;Holly et al 2010;Gattini and Hiebert, 2010;Corradin and Fontana, 2013;Liu, 2015;Turk, 2015;Kulikauskas, 2016), others do not (e.g. Malpezzi, 1999;Gallin, 2006;Zhou and Sornette, 2006;Mikhed and Zem ík, 2009;Clark and Coggin, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Majority of the studies concentrate either on a single country (e.g. Gimeno and Martínez-Carrascal, 2006;Oikarinen, 2009;Turk, 2015), a panel limited to a fraction of euro area countries (Annett, 2005;European Commission, 2012;Kulikauskas, 2016;Zhu et al, 2017) 10 or analyze aggregated euro area time series (Gattini and Hiebert, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%